2019
DOI: 10.7759/cureus.5627
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment Between High-resolution Ultrasonography and Field Magnetic Resonance Imaging in Supraspinatus Tear Cases and Its Arthroscopic Correlation

Abstract: BackgroundDiagnosis of a supraspinatus tear in patients presenting with shoulder pain is a difficult task and often requires the help of an MRI. However, in recent years, high-resolution ultrasonography (USG) has been utilized as a cheaper yet sensitive alternative. The aim of the study is to provide a comparative assessment of supraspinatus tears between USG and MRI in relation to arthroscopic results.MethodsA total of 60 patients with shoulder pain for the last three months or more scheduled to undergo arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Out of 92 patients, 44 (47.8%) patients were males while 48 (52.2%) patients were females. Subharwal et al9 had 68.3% females and 32.7% males' patients in their study.…”
mentioning
confidence: 77%
“…Out of 92 patients, 44 (47.8%) patients were males while 48 (52.2%) patients were females. Subharwal et al9 had 68.3% females and 32.7% males' patients in their study.…”
mentioning
confidence: 77%
“…27 Five studies evaluated in this review included US and MRI diagnostic outcome data with arthroscopy as reference. 2,10,15,47,50 After meta-analysis, no significant differences were found in US and MRI diagnostic sensitivity, specificity, and accuracy for any sized-thickness, fullthickness, or partial-thickness supraspinatus tears (Figure 4). These results are consistent with those of recent systematic reviews and meta-analyses.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the mean time from US examination to arthroscopic evaluation was >6 months in 3 studies 2 , 15 , 44 and was not reported in another 8 studies. 10 , 17 , 24 , 30 , 40 , 48 , 50 , 57 Variability in time from patient presentation to surgery could influence the correlation between US results and arthroscopy because of subsequent healing or further damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation